The forecasting of operating results of fish processing enterprises: problems and methodological approaches to their solving - O. А. Shikhova; M. N. Selina; V. M. Selin (Статистика и экономика, 2019)
The basic methodological aspects and approbation results of forecasting and planning of the sales volumes of a fish processing enterprise, depending from a natural and climatic factor (environmental temperature) are considered in the article through the example of the groups of companies “Art-fish” of Vologda city. The dependence of volume of consumer demand for products of the fish processing enterprise from the ambient temperature regime is educed. The methods of building of a regression model between time series of the studied indexes and the order of calculation of forecasting levels of daily revenue are described. The economic model of the dynamic dependence of daily revenue of fish product sales from the average environmental temperature is built. The forecasts of the revenue levels of sales taking into account the dynamics influence of the average daily temperature of the environment and the weekly cycle of its fluctuations are received. The presented methods of modeling and forecasting of the level of daily revenue will allow taking reasonable decisions in practice for evaluation of planned values of product procurement for sale within a short-term upcoming period; that is timely in the conditions of fast-changing consumer market.Purpose was in finding and modeling of the dynamic dependence of daily revenue of sales of the fish-processing enterprise from the fluctuations of the ambient temperature regime and the development of the methods of its forecasting.Materials and methods. As part of the study the methods of econometric modeling were used in complex based on the time series, including the building of the trend models, models with a cyclical component, regression models. The indexes of the operating results of the group of companies “Art-fish” of Vologda city served as the primary data. They were taken from the bases of the mentioned enterprises. The indexes of the temperature regime of the environment were received from the Weather journal of the official website of weather forecast Gismeteo.Results. The research required quite a deep study of the character and peculiarities of the dynamics of the indexes of daily revenue and preparation of the data for modeling. While studying the regularities of interdependent dynamics of the indexes of revenue and environmental temperature the number of important conclusions were received that consequently defined the methods of building of the regression model and the order of calculation of the forecasting levels. The presence of the firm inverse correlation between the trend of the daily revenue and environmental temperature was educed. Herewith the analysis of the results of forecasting using the received models showed that the forecast accuracy, both point and interval with a weakening of the strength of the manifestation of the correlation dependence between the signs does not decrease. According to the results of correlation-regression analysis the methods of forecasting of the levels of daily revenue for fish-processing enterprises were suggested which would allow taking reasonable decisions for evaluation of the planned volumes of product procurement for sale within a short-term upcoming period that was timely in the conditions of a fast-changing consumer market.Conclusion. As the studies showed, consumer demand for the products of fish processing enterprises flexibly responded to the change of the ambient temperature. This fact allowed developing the methodological approaches to the forecasting of the levels of daily revenue that was absolutely necessary for taking reasonable decisions on planning of the volumes of procurement and output of production for a short- term upcoming period. In the contemporary market conditions and uncertainty the possibility to plan production and financial activities for processing enterprises of food industry is especially currently topical.